2022
DOI: 10.1136/jim-2021-002017
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Pro-Brain Natriuretic Peptide is an Independent Predictor of Mortality in Patients with Sepsis

Abstract: This study aims to evaluate the role of cardiac enzymes N-terminal pro-brain natriuretic peptide (NT-proBNP) and cardiac troponin-I (CTnI) as predictors of outcomes in patients with sepsis.78 cases with a diagnosis of sepsis were enrolled over a 2-year period. Baseline demographic, Acute Physiology and Chronic Health Evaluation-II (APACHE-II), Simplified Acute Physiology Score-II (SAPS-II), hematologic and biochemical parameters were noted. Serum NT-proBNP and CTnI were evaluated at 24 and 72 hours of admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Therefore, it can be suggested that its expression level in sepsis patients is significantly higher than that in nonsepsis patients [ 10 , 11 ]. Secondly, its higher concentration level in the death group also indicates that the degree of external infection is more serious, and the stimulation of myocardial cells is more intense, thus causing the continuous increase of serum BNP level [ 12 ]. Lac is a product of metabolism in the absence of oxygen in human body, and its expression level is relatively low in normal body environment.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, it can be suggested that its expression level in sepsis patients is significantly higher than that in nonsepsis patients [ 10 , 11 ]. Secondly, its higher concentration level in the death group also indicates that the degree of external infection is more serious, and the stimulation of myocardial cells is more intense, thus causing the continuous increase of serum BNP level [ 12 ]. Lac is a product of metabolism in the absence of oxygen in human body, and its expression level is relatively low in normal body environment.…”
Section: Related Workmentioning
confidence: 99%
“…In a small prospective study, N-terminal probrain natriuretic peptide (NT-proBNP) values at 72 h were an independent predictor of mortality in patients with sepsis ( Biswas et al, 2022 ). NT-proBNP has not been studied in septic encephalopathy.…”
Section: Indicators Of Sepsis and Septic Encephalopathymentioning
confidence: 99%
“…NT-proBNP является независимым фактором риска смертности у ожоговых больных с сепсисом [97]. Комбинация NT-proBNP с показателями клинического риска пациентов повышает прогностическую значимость [98].…”
Section: мозговой натрийуретический пептидunclassified